Cone-beam computed tomography study of root and root canal morphology using new classification in three ethnic groups in Kelantan, Malaysia - Karobari, Mohmed Isaqali (2020)
Adequate knowledge and comprehensive understanding of the root canal system is an essential pre-requisite for endodontic treatment. It is a general conviction that both maxillary and mandibular anterior teeth have single roots encasing single canals. However, literature shows higher prevalence of two canals in mandibular incisors which varies according to ethnicity, gender and age. Hence the aim of this study was to evaluate the root and canal morphology in Malaysian sub-population using cone beam computed tomography (CBCT) interpreted using two different classification systems. CBCT images of 856 patients with age ranging from 14 to 70 years, having 10080 anteriors were examined using software Romexis ver.2.9 (Planmeca Promax 3D). The number of roots and the root canal morphology of permanent anterior teeth were determined in different planes [coronal, axial and sagittal] and classified using Vertucci’s and Ahmed et al classification systems. Pearson Chi-square/Fisher’s exact tests were used for statistical analysis (P=0.05). According to Ahmed et al and Vertucci’s classifications, code 1MA1(MA- maxillary anteriors) and Type I were the most common in maxillary anteriors (98.2%), mandibular central incisors (64.7%) and canines (90.5%) respectively, whereas code 1MD1-2-1 (MD- mandibular anteriors) and Type III were the most common in mandibular lateral incisors (51%). Several Vertucci’s non-classifiable variations were identified which were classified using the new system. These include codes 1MD2-1-2-1(2.1%), and 1MD2-1-2-1-2-1 (0.1%). Two-rooted mandibular canines were identified in six samples. The prevalence of root canal variations in mandibular incisors was higher in males compared to females (P<0.001), Malay followed by Chinese and Indians (P<0.001), and in 20-30 age group as compared to other age groups (P<0.001). No significant difference was found in maxillary anteriors. Mandibular anteriors show a wide range of root and canal anatomical variations. The complexity of the root canal configuration is significantly affected by sex, ethnicity and age. The new classification system provides a simple and accurate presentation of the root canal morphology, especially in cases where complex root canal morphology is present.